Evaluation of the risks of chemotherapy in dogs with thrombocytopenia. (10th April 2015) - Finlay, J.; Wyatt, K.; Black, M.
Abstract: Thrombocytopenia is commonly encountered in veterinary oncology. Currently, there are no standard guidelines regarding the administration of chemotherapy to the patients with thrombocytopenia. This observational epidemiological cohort study aimed to determine whether thrombocytopenic dogs were at increased risk of gastrointestinal adverse effects (vomiting, diarrhoea, inappetence) or haemorrhage following administration of standard doses of chemotherapy. The adverse effects following 77 prospectively identified episodes of thrombocytopenia (platelet count, <200 000 µL −1 ) were compared with the adverse effects experienced in a retrospective cohort (platelet count >200 000 µL −1 ), and evaluated by statistical analysis. Overall, there was no statistically significant difference in the incidence of gastrointestinal adverse effects or haemorrhage between thrombocytopenic and control dogs. The control group of dogs with lymphoma were statistically more likely to experience vomiting as an adverse effect of chemotherapy ( P = 0.028). The results presented here showed no evidence for an increased risk of gastrointestinal adverse effects or haemorrhage in thrombocytopenic dogs after receiving standard doses of chemotherapy.